2015
DOI: 10.1007/s11845-015-1313-6
|View full text |Cite
|
Sign up to set email alerts
|

Concussion in rugby: knowledge and attitudes of players

Abstract: Despite good knowledge of concussion complications, management players engage in unsafe behaviour with little difference between gender and competition grades. Information regarding symptoms and management should be available to all players, coaches, and parents. Provision of medical care should be mandatory at every level of competition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
21
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 17 publications
1
21
1
Order By: Relevance
“…This study sample (294 participants) is substantially larger when compared to other studies that investigated concussion knowledge among rugby players. [8,9,11,12] Only 46% of the total study sample had previously received information on concussion, which is marginally more than the 39% informed participants reported for Italian rugby players. [8] A better-informed sample was reported by Sye et al, [7] where 61% of their participants had received concussion information.…”
Section: Discussionmentioning
confidence: 94%
“…This study sample (294 participants) is substantially larger when compared to other studies that investigated concussion knowledge among rugby players. [8,9,11,12] Only 46% of the total study sample had previously received information on concussion, which is marginally more than the 39% informed participants reported for Italian rugby players. [8] A better-informed sample was reported by Sye et al, [7] where 61% of their participants had received concussion information.…”
Section: Discussionmentioning
confidence: 94%
“…The above-mentioned statement is supported by studies done by O'Connell and Molloy and Delahunty et al, in which respectively 75% and 73% of the players indicated that they would play with a concussion in important matches. [5,11] The main reason for wanting to continue was the fear of letting their teammates down. Although these factors play a role, a player with a good concussion attitude may still choose to act in an incorrect or unsafe manner following concussion without being influenced.…”
Section: Discussionmentioning
confidence: 99%
“…These findings support the claims in the study by O'Connell and Molloy namely, that players are influenced by important matches. [5] Viljoen highlights that there needs to be educational workshops on concussion conducted specifically for rugby players. [3] Compared to the study done by Viljoen , [3] this present study has shown superior results with regards to concussion knowledge and attitudes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…(Tables 5&6) 1,2 Concussed Irish soccer players are less inclined to continue playing in an important game than their amateur rugby union counterparts (4.3% versus 76.0%). 3 Conclusion Safer attitudes surrounding concussion are related to increasing player age, not necessarily playing experience. Higher player knowledge does not necessarily confer safer attitudes towards concussion.…”
mentioning
confidence: 99%